Design and application of artificial rare L-lysine codons in Corynebacterium glutamicum - Yang, Cuiping; Peng, Zehao; Yang, Lu; Du, Bowen; Guo, Chuanzhuang; Sui, Songsen; Wang, Jianbin; Li, Junlin; Wang, Junqing; Li, Nan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: L-lysine is widely used in the feed, food, and pharmaceutical industries, and screening for high L-lysine-producing strains has become a key goal for the industry. Methods: We constructed the rare L-lysine codon AAA by corresponding tRNA promoter replacement in Corynebacterium glutamicum. Additionally, a screening marker related to the intracellular L-lysine content was constructed by converting all L-lysine codons of enhanced green fluorescent protein (EGFP) into the artificial rare codon AAA. The artificial EGFP was then ligated into pEC-XK99E and transformed into competent C. glutamicum 23604 cells with the rare L-lysine codon. After atmospheric and room-temperature plasma mutation and induction culture, 55 mutants (0.01% of total cells) with stronger fluorescence were sorted using flow cytometry, and further screened by fermentation in a 96-deep-well plate and 500 mL shaker. Results: The fermentation results showed that the L-lysine production was increased by up to 9.7% in the mutant strains with higher fluorescence intensities, and that the highest screening positive rate was 69%, compared with that in the wild-type strain. Conclusion: The application of artificially constructed rare codons in this study represents an efficient, accurate, and simple method for screening other amino acid-producing microorganisms.